2018
DOI: 10.1002/sdr.1589
|View full text |Cite
|
Sign up to set email alerts
|

Using integrated modeling to support the global eradication of vaccine‐preventable diseases

Abstract: The long‐term management of global disease eradication initiatives involves numerous inherently dynamic processes, health and economic trade‐offs, significant uncertainty and variability, rare events with big consequences, complex and interrelated decisions, and a requirement for cooperation among a large number of stakeholders. Over the course of more than 16 years of collaborative modeling efforts to support the Global Polio Eradication Initiative, we developed increasingly complex integrated system dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 99 publications
(162 reference statements)
0
24
0
Order By: Relevance
“…Following the search process shown in Figure 1 , the systematic literature review and addition of other studies by the three GPEI-supported modeling groups led to the extraction of information from 176 included studies [ 1 - 4 , 8 - 179 ]. As noted, during review of the full text of the studies identified by the search, we excluded papers that presented statistical analyses that did not include a mechanistic poliovirus transmission model [ 180 187 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the search process shown in Figure 1 , the systematic literature review and addition of other studies by the three GPEI-supported modeling groups led to the extraction of information from 176 included studies [ 1 - 4 , 8 - 179 ]. As noted, during review of the full text of the studies identified by the search, we excluded papers that presented statistical analyses that did not include a mechanistic poliovirus transmission model [ 180 187 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 provides an overview of some of the attributes of the model structures and assumptions for the 83 papers that included a poliovirus transmission model [ 4 , 9 , 10 , 14 , 18 20 , 22 , 24 27 , 33 36 , 38 41 , 43 , 46 , 47 , 49 62 , 64 , 65 , 68 71 , 73 77 , 81 , 97 100 , 129 , 132 135 , 147 171 ] organized by modeling group. Mathematical models for poliovirus transmission vary considerably in their complexity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, optimization models are excellent for quickly uncovering optimal policies. A hybrid approach can take advantage of the above complementary methods’ strengths (Duintjer Tebbens and Thompson, ).…”
Section: Advantages Of Hybridsmentioning
confidence: 99%
“…In the same issue, for example, Ghaffarzadegan and Larson () show how traditional operations research (OR) models can benefit by including feedback processes. Additionally, Duintjer Tebbens and Thompson () argue for more integrated modeling for healthcare studies and its value to appropriately address complex policy decisions. The authors present results of more than a decade of their efforts in producing complex integrated SD models that combine numerous analytical methods and discuss practical challenges of integrating different analytical tools.…”
Section: Introductionmentioning
confidence: 99%